Transparent conductive film containing double-layer grid structure and preparation method thereof
By forming a double-layer structure of copper grid and BaSnO3 grid on a transparent flexible substrate, magnetron sputtering technology combined with the advantages of both, the problem of the carrier concentration of ITO film is close to the limit, and a high-performance and low-cost transparent conductive film is achieved.
Patent Information
- Application Number
- CN202510422017.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-07
AI Technical Summary
The carrier concentration of the existing ITO films has approached the limit, resulting in a decrease in transmittance. Indium has high toxicity, high price and low stability, making it difficult to meet the needs of new transparent conductive films.
Magnetically controlled sputtering technology is used to combine the copper grid with the BaSnO3 grid to form a transparent conductive film with a double-layer grid structure. By combining the density of the copper grid and the high permeability of the BaSnO3 grid, a high-performance transparent conductive film is prepared.
It realizes a high-performance transparent conductive film, maintains excellent photoelectric performance and stability, and reduces the production cost. It is suitable for transparent conductive devices, flexible displays and functional inorganic coatings and other fields.
Smart Images

Figure CN119920539A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of transparent conductive films, in particular to a transparent conductive film containing a double-layer grid structure and a preparation method thereof. Background Art
[0002] Transparent conductive film refers to a conductive film with a transmittance greater than 80% and a film resistance less than 15Ω / sq in the visible light wavelength of 380-800nm. With the rapid development of science and technology and the improvement of people's lives, the application of new display devices, high-power solar cells, large-size outdoor displays, energy-saving infrared reflective films, etc. has become more and more extensive, which has led to an increasing demand for transparent conductive films. At present, the most widely used transparent conductive film in the market is In2O3 doped with Sn, that is, ITO film. ITO film has excellent optoelectronic properties and has long been a dominant transparent conductive film in the application of optoelectronic devices. However, the carrier concentration of ITO film development has basically reached its limit, and films with high carrier concentrations will reduce optical properties such as transmittance. At the same time, indium has problems such as high toxicity, high price, low stability, and easy reduction. Therefore, it is urgent to find a new transparent conductive film that can not only maintain the same or higher level of optoelectronic performance as ITO, but also be low-priced and highly stable.
[0003] The electron effective mass of BaSnO3 is small, and the Hall mobility of BaSnO3-based films is higher than that of ITO films, which makes BaSnO3-based films have higher field effect mobility and higher conductivity. At the same time, the oxygen chemical diffusion coefficient of BaSnO3-based films is lower, and it has better thermal stability than ITO films, and can maintain excellent photoelectric properties in the air for a long time. Compared with strategic In2O3 materials, Ba and Sn elements are abundant in reserves and can be used for a long time.
[0004] Based on this, how to prepare BaSnO3-based thin films with excellent performance has become the research focus of scholars at home and abroad. Summary of the invention
[0005] In order to address the deficiencies in the prior art, the present invention provides a transparent conductive film containing a double-layer grid structure and a preparation method thereof, which uses magnetron sputtering technology to combine the high conductivity of a copper grid with the high permeability of a BaSnO3 grid, thereby preparing a high-performance transparent conductive film with low overall preparation cost. The product has good applications in transparent conductive components, transparent flexible heaters, flexible displays, functional inorganic coatings and other fields.
[0006] In order to achieve the above object, the specific scheme adopted by the present invention is: In one aspect, the present invention discloses a method for preparing a transparent conductive film having a double-layer grid structure, comprising the following steps: Step 1: Clean the transparent flexible substrate, and after the transparent flexible substrate is dried, prepare a copper film on the surface of the transparent flexible substrate by using vacuum coating technology; Step 2: using a self-cracking agent to prepare a layer of self-cracking film on the surface of the copper film, drying it at room temperature to 80° C., so that the self-cracking film naturally cracks to form a mesh-like cracking template; Step 3, using magnetron sputtering technology to prepare a layer of BaSnO3 film on the mesh cracking template; Step 4: Use acetone and ultrasonic cleaning to remove the self-cracking film on the copper film, thereby obtaining a BaSnO3 grid; Step 5: Spray etching solution onto the surface of the BaSnO3 grid and seal it to let it stand to etch the copper film into a copper grid, thereby obtaining a transparent conductive film with a double-layer grid structure.
[0007] Furthermore, in step 1, the transparent flexible substrate is a flexible glass or a transparent flexible plastic with a thickness of 30-120 μm.
[0008] Furthermore, in step one, the vacuum coating technology is magnetron sputtering coating, thermal evaporation coating or pulsed laser deposition.
[0009] Furthermore, in step 2, the self-cracking agent is any one of pure acrylic emulsion, silicone acrylic emulsion, acrylic acid emulsion or nail polish.
[0010] Furthermore, in step 2, the thickness of the self-cracking film is 5-15 μm.
[0011] Furthermore, in step 2, a self-cleaving film is prepared by a Czochralski coating method or a spin coating method.
[0012] Furthermore, in step three, a layer of BaSnO3 thin film is prepared on the mesh cracking template and on the outer peripheral surface of the copper film using magnetron sputtering technology.
[0013] Furthermore, in step five, the etching solution is evenly sprayed onto the surface of the BaSnO3 grid and sealed and allowed to stand for 2 to 10 minutes. The etching solution used is a FeCl3 solution with a concentration of 10 to 40%. The etching temperature is controlled to be 40 to 60°C. After the etching is completed, it is cleaned with deionized water and alcohol to remove the etching solution.
[0014] On the other hand, the present invention discloses a transparent conductive film containing a double-layer grid structure, including a transparent flexible substrate and a double-layer grid structure arranged on the transparent flexible substrate, wherein the double-layer grid structure is composited by a copper grid and a BaSnO3 grid, and the BaSnO3 grid covers the top surface of the copper grid.
[0015] Furthermore, the thickness of the copper grid is 100-200 nm, and the thickness of the BaSnO3 grid is 50-200 nm.
[0016] Beneficial effects: (1) When preparing a transparent conductive film, the present invention first uses vacuum coating technology to deposit a dense copper film on the surface of a transparent flexible substrate; then prepare a self-cracking film on the surface of the copper film, and the self-cracking film naturally cracks to form a mesh-like cracking template; then prepare a BaSnO3 film on the mesh-like cracking template, remove the self-cracking film to obtain a continuous BaSnO3 grid, and finally spray an etching liquid on the surface of the BaSnO3 grid and seal it for a period of time to etch the copper film into a copper grid, thereby obtaining a transparent conductive film with a double-layer grid structure. The transparent conductive film of the present invention is a copper grid and a BaSnO3 grid formed on the surface of a transparent flexible substrate, wherein the copper grid has good compactness and good conductivity, the bottom surface of the copper grid is covered by the transparent flexible substrate, and the top surface is covered by the BaSnO3 grid, so that the copper grid is not easily oxidized, and intermolecular connections are formed between the film layers of the transparent conductive film, so that the photoelectric performance and stability of the transparent conductive film are excellent.
[0017] (2) The present invention uses a self-cracking agent to prepare a layer of self-cracking film on the surface of the copper film, and dries it at a temperature of room temperature to 80°C, so that the self-cracking film naturally cracks to form a mesh cracking template, which has the following advantages: (I) In the prior art (such as patent CN104993057B), the preparation process of the cracking agent is relatively complicated. The self-cracking agent of the present invention directly uses any one of pure acrylic emulsion, silicone acrylic emulsion, acrylic emulsion or nail polish, without the need for a cumbersome preparation process, which greatly simplifies the operation process and improves work efficiency. (II) In the prior art, the cracking of the cracking film requires the control of specific temperature, humidity and time conditions, and the precise control of these conditions increases the complexity and time cost of the operation. The self-cracking film of the present invention can achieve natural cracking in a wide temperature range from room temperature to 80°C, without the need to strictly control environmental conditions, thereby improving the cracking efficiency.
[0018] (3) In order to further improve the performance of the transparent conductive film in the present invention, when preparing the BaSnO3 film, in addition to preparing the BaSnO3 film on the mesh crack template, the BaSnO3 film is also prepared on the outer peripheral surface of the copper film. This can prevent the outer peripheral surface of the copper mesh from being oxidized, thereby making the performance of the transparent conductive film better.
[0019] (4) The present invention uses an etching solution to treat the copper film to prepare a copper grid, which has the following advantages: (I) The main component of the etching solution is a FeCl3 solution with a concentration of 10-40%, which can effectively and selectively react with unwanted copper without chemically reacting with the transparent flexible substrate and the BaSnO3 grid. This high selectivity ensures the accuracy of the etching process and avoids damage to materials other than the target structure, thereby ensuring the quality and performance of the final product. (II) The etching rate of copper can be easily controlled by adjusting the concentration of FeCl3 in the etching solution. The higher the concentration, the faster the etching rate, which provides great convenience for time management and efficiency improvement in the production process. This controllability enables manufacturers to quickly adjust process parameters according to specific needs to meet the requirements of different application scenarios. (III) The etching process only requires the etching solution to be evenly sprayed on the surface of the BaSnO3 grid and sealed and left to stand for 2-10 minutes, without the need for complex equipment or steps. In addition, after the etching is completed, the etching solution can be removed by washing with deionized water and alcohol. These cleaning materials are easy to obtain and harmless to the environment, meeting the requirements of green production. (IV) The etching process is carried out in the temperature range of 40~60℃, which is neither too high to cause thermal damage to the material nor too low to affect the etching efficiency. This temperature adaptability makes the etching process more flexible and can adapt to different production environments and conditions. (V) Due to the high precision and controllability of the etching process, the final transparent conductive film with a double-layer grid structure has excellent performance. This film not only maintains the original characteristics of the BaSnO3 grid, but also achieves better light transmittance by removing excess copper, making it suitable for various electronic devices and optical applications.
[0020] (5) The transparent conductive film product prepared by the present invention has high reliability and low cost, is suitable for industrial production, and is particularly suitable for use in transparent conductive devices, transparent flexible heaters, flexible display fields, and functional inorganic coating fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic cross-sectional view of the transparent conductive film prepared by the present invention.
[0022] Figure 2 This is a surface structure diagram of the transparent conductive film prepared in Example 1. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] The present invention provides a transparent conductive film with a double-layer grid structure and a preparation method thereof, please refer to Figure 1 The transparent conductive film includes a transparent flexible substrate and a double-layer grid structure arranged on the transparent flexible substrate. The double-layer grid structure is composed of a copper grid and a BaSnO3 grid. The bottom copper grid provides a conductive path for the BaSnO3 grid, and the copper grid prepared by vacuum coating technology has good compactness. The bottom surface of the copper grid is covered by a transparent flexible substrate, and the top surface is covered by a BaSnO3 grid. The copper grid is not easily oxidized, and intermolecular connections are formed between the layers of the transparent conductive film. The transparent conductive film has excellent stability. Overall, the transparent conductive film has low cost, compact structure, and stable performance. Its preparation method mainly includes the following steps: Step 1: clean the transparent flexible substrate with alcohol, acetone, etc., and after the transparent flexible substrate is dried, prepare a copper film with a thickness of 100-200 nm on the surface of the transparent flexible substrate by using vacuum coating technology. Directly coating the copper film on the surface of the transparent flexible substrate is conducive to forming an intermolecular connection between the copper film and the transparent flexible substrate, which can greatly enhance the conductivity and reliability of the transparent conductive film; wherein, the transparent flexible substrate can be a material such as flexible glass, transparent flexible plastic, etc., and the vacuum coating technology can be a coating scheme such as magnetron sputtering coating, thermal evaporation coating or pulsed laser deposition; Step 2: After step 1 is completed, a 5-15 μm thick self-cracking film is prepared on the surface of the copper film using a self-cracking agent, and the film is dried at room temperature to 80°C to allow the self-cracking film to naturally crack and form a mesh cracking template; the self-cracking film is selected here to obtain a mesh cracking template, so as to facilitate the subsequent preparation of copper grids and BaSnO3 grids; and the selection of any one of pure acrylic emulsion, silicone acrylic emulsion, acrylic emulsion or nail polish as a self-cracking agent has the advantages of simple process and easy operation; the preparation method of the self-cracking film can adopt a liquid phase coating method such as pull coating and spin coating; Step 3: Using magnetron sputtering technology, a BaSnO3 film with a thickness of 50-200 nm is prepared on the mesh cracking template and the outer peripheral surface of the copper film; Step 4: Use acetone and ultrasonic cleaning to remove the self-cracking film on the copper film, so as to obtain a BaSnO3 grid; the formed BaSnO3 grid is coated on the surface of the copper grid, so that only the inner wall of each grid inside the copper grid is exposed, but because the thickness of the copper grid is very thin, only no more than 200nm, the total area of the copper grid exposed to the outside is small, which can greatly reduce the contact area between the copper grid and the outside air, thereby ensuring that the copper grid is not easily oxidized, and at the same time can also improve the conductivity and transmittance of the transparent conductive film to a certain extent; Step 5. Spray the etching solution evenly on the surface of the BaSnO3 grid and seal it for 2 to 10 minutes. The etching solution mainly reacts with unnecessary copper and does not react with the transparent flexible substrate and the BaSnO3 grid. The etching solution used is a FeCl3 solution with a concentration of 10 to 40%. The higher the concentration of FeCl3 in the etching solution, the faster the copper etching speed. The etching temperature is controlled at 40 to 60°C. After etching, it is cleaned with deionized water and alcohol to remove the etching solution to obtain a transparent conductive film with a double-layer grid structure.
[0025] It should be noted that the transmittance and resistance of the transparent conductive film can be regulated by the following methods: (1) Regulating the thickness of the copper film: The thicker the copper film, the better the conductivity of the transparent conductive film, but its transmittance and stability will decrease; (2) Regulating the thickness of the BaSnO3 film: The thicker the BaSnO3 film, the lower the transmittance of the transparent conductive film; (3) Regulating the thickness of the self-cracking film: The thicker the self-cracking film, the smaller the crack grid density, and the BaSnO3 grid density will also decrease in the later stage, and the transmittance and resistance will decrease accordingly.
[0026] The technical solution of the present invention is further described below in conjunction with specific embodiments and comparative examples.
[0027] Example 1 A method for preparing a transparent conductive film having a double-layer grid structure mainly comprises the following steps: Step 1: Clean the transparent flexible substrate (flexible glass) with alcohol. After the transparent flexible substrate is dried, a copper film is prepared on the surface of the transparent flexible substrate by magnetron sputtering coating. When performing magnetron sputtering coating, the background vacuum of the magnetron sputtering system is pumped to 1.0×10 -3 Pa, high-purity (99.999%) argon gas was introduced, the pressure was adjusted to 1.0 Pa, the distance between the fixed target and the substrate was 10 cm, the sputtering power was 100 W, the metal copper target was sputtered, and a 200 nm thick copper film was deposited; Step 2: A self-cracking agent is selected from acrylic emulsion, and a self-cracking film with a thickness of 15 μm is prepared on the surface of the copper film by a pulling coating method, and the film is dried at a temperature of 80° C. to allow the self-cracking film to naturally crack to form a mesh cracking template; the pulling speed is 5 cm / min; the average mesh diameter of the cracks in the mesh cracking template is 100 μm, and the cracking grid line width is 5-8 μm; Step 3: Place the semi-finished product obtained in step 2 on the sample stage of the magnetron sputtering system and pump the background vacuum of the magnetron sputtering system to 1.0×10 -3Pa, high-purity (99.999%) argon gas was introduced, the pressure was adjusted to 1.0 Pa, the distance between the fixed target and the substrate was 10 cm, the sputtering power was 100 W, the ceramic BaSnO3 target was sputtered, and a 200 nm thick BaSnO3 film was deposited at room temperature; Step 4: Use acetone and ultrasonic cleaning to remove the self-cracking film on the copper film. After cleaning, a BaSnO3 grid can be obtained; Step 5: Spray the etching solution evenly onto the surface of the BaSnO3 grid and seal it for 2 minutes. The etching solution used is a 40% FeCl3 solution. The etching temperature is controlled at 60°C. After etching, it is washed with deionized water and alcohol to remove the etching solution to obtain a transparent conductive film with a double-layer grid structure.
[0028] refer to Figure 2 It can be seen that in the transparent conductive film prepared in this embodiment, the line width of the BaSnO3 grid is relatively uniform and has good continuity.
[0029] Example 2 A method for preparing a transparent conductive film having a double-layer grid structure mainly comprises the following steps: Step 1: Clean the transparent flexible substrate (flexible glass) with acetone. After the transparent flexible substrate is dried, a copper film is prepared on the surface of the transparent flexible substrate by magnetron sputtering coating. When performing magnetron sputtering coating, the background vacuum of the magnetron sputtering system is pumped to 1.0×10 -3 Pa, high-purity (99.999%) argon gas was introduced, the pressure was adjusted to 1.0 Pa, the distance between the target and the substrate was fixed at 10 cm, the sputtering power was 100 W, the metal copper target was sputtered, and a 150 nm thick copper film was deposited; Step 2: a self-cracking agent is selected from nail polish, and a self-cracking film with a thickness of 8 μm is prepared on the surface of the copper film by a pulling coating method, and dried at a temperature of 40° C. to make the self-cracking film naturally crack to form a mesh cracking template; the pulling speed is 11 cm / min; the average mesh diameter of the cracks in the mesh cracking template is 80 μm, and the cracking grid line width is 6-10 μm; Step 3: Place the semi-finished product obtained in step 2 on the sample stage of the magnetron sputtering system and pump the background vacuum of the magnetron sputtering system to 1.0×10 -3 Pa, high-purity (99.999%) argon gas was introduced, the pressure was adjusted to 1.0 Pa, the distance between the target and the substrate was fixed at 10 cm, the sputtering power was 100 W, the ceramic BaSnO3 target was sputtered to obtain a 150 nm thick BaSnO3 film, and the deposition temperature was room temperature; Step 4: Use acetone and ultrasonic cleaning to remove the self-cracking film on the copper film. After cleaning, a BaSnO3 grid can be obtained; Step 5: Spray the etching solution evenly onto the surface of the BaSnO3 grid and seal it for 5 minutes. The etching solution used is a 20% FeCl3 solution. The etching temperature is controlled at 50°C. After etching, it is washed with deionized water and alcohol to remove the etching solution to obtain a transparent conductive film with a double-layer grid structure.
[0030] Example 3 A method for preparing a transparent conductive film having a double-layer grid structure mainly comprises the following steps: Step 1: Clean the transparent flexible substrate (transparent flexible plastic) with alcohol. After the transparent flexible substrate is dried, a copper film is prepared on the surface of the transparent flexible substrate by magnetron sputtering coating. When performing magnetron sputtering coating, the background vacuum of the magnetron sputtering system is pumped to 1.0×10 -3 Pa, high-purity (99.999%) argon gas was introduced, the pressure was adjusted to 1.0 Pa, the distance between the target and the substrate was fixed at 10 cm, the sputtering power was 100 W, the metal copper target was sputtered, and a 120 nm thick copper film was deposited; Step 2: a self-cracking agent is selected from nail polish, and a self-cracking film with a thickness of 12 μm is prepared on the surface of the copper film by a pulling coating method, and dried at a temperature of 50° C. to make the self-cracking film naturally crack to form a mesh cracking template; the pulling speed is 8 cm / min; the average mesh diameter of the cracks in the mesh cracking template is 90 μm, and the cracking grid line width is 6-12 μm; Step 3: Place the semi-finished product obtained in step 2 on the sample stage of the magnetron sputtering system and pump the background vacuum of the magnetron sputtering system to 1.0×10 -3 Pa, high-purity (99.999%) argon gas was introduced, the pressure was adjusted to 1.0 Pa, the distance between the target and the substrate was fixed at 10 cm, the sputtering power was 100 W, the ceramic BaSnO3 target was sputtered, and a 120 nm thick BaSnO3 film was obtained. The deposition temperature was room temperature; Step 4: Use acetone and ultrasonic cleaning to remove the self-cracking film on the copper film. After cleaning, a BaSnO3 grid can be obtained; Step 5: Spray the etching solution evenly onto the surface of the BaSnO3 grid and seal it for 10 minutes. The etching solution used is a 10% FeCl3 solution. The etching temperature is controlled at 40°C. After etching, it is washed with deionized water and alcohol to remove the etching solution to obtain a transparent conductive film with a double-layer grid structure.
[0031] Example 4 A method for preparing a transparent conductive film having a double-layer grid structure mainly comprises the following steps: Step 1: Clean the transparent flexible substrate (transparent flexible plastic) with acetone. After the transparent flexible substrate is dried, a copper film is prepared on the surface of the transparent flexible substrate by magnetron sputtering coating. When performing magnetron sputtering coating, the background vacuum of the magnetron sputtering system is pumped to 1.0×10 -3 Pa, high-purity (99.999%) argon gas was introduced, the pressure was adjusted to 1.0 Pa, the distance between the target and the substrate was fixed at 10 cm, the sputtering power was 100 W, the metal copper target was sputtered, and a 100 nm thick copper film was deposited; Step 2: A self-cracking agent is selected from acrylic emulsion, and a self-cracking film with a thickness of 5 μm is prepared on the surface of the copper film by a pulling coating method, and the film is dried at a temperature of 60° C. to allow the self-cracking film to naturally crack to form a mesh cracking template; the pulling speed is 15 cm / min; the average mesh diameter of the cracks in the mesh cracking template is 60 μm, and the cracking grid line width is 4-7 μm; Step 3: Place the semi-finished product obtained in step 2 on the sample stage of the magnetron sputtering system and pump the background vacuum of the magnetron sputtering system to 1.0×10 -3 Pa, high-purity (99.999%) argon gas was introduced, the pressure was adjusted to 1.0 Pa, the distance between the fixed target and the substrate was 10 cm, the sputtering power was 100 W, the ceramic BaSnO3 target was sputtered to obtain a 100 nm thick BaSnO3 film, and the deposition temperature was room temperature; Step 4: Use acetone and ultrasonic cleaning to remove the self-cracking film on the copper film. After cleaning, a BaSnO3 grid can be obtained; Step 5: Spray the etching solution evenly onto the surface of the BaSnO3 grid and seal it for 8 minutes. The etching solution used is a 25% FeCl3 solution. The etching temperature is controlled at 55°C. After etching, it is washed with deionized water and alcohol to remove the etching solution to obtain a transparent conductive film with a double-layer grid structure.
[0032] Example 5 A method for preparing a transparent conductive film having a double-layer grid structure mainly comprises the following steps: Step 1: Clean the transparent flexible substrate (flexible glass) with alcohol and acetone. After the transparent flexible substrate is dried, a copper film is prepared on the surface of the transparent flexible substrate using vacuum thermal evaporation technology. When performing thermal evaporation coating, the background vacuum of the magnetron sputtering system is pumped to 1.0×10 -3 Pa, the heating current is adjusted to 100A, the metal copper particles are evaporated, and a 100nm thick copper film is deposited; Step 2: A self-cracking agent is pure acrylic emulsion, and a self-cracking film with a thickness of 9 μm is prepared on the surface of the copper film by spin coating, and dried at a temperature of 30° C. to allow the self-cracking film to naturally crack to form a mesh cracking template; the average mesh diameter of the cracks in the mesh cracking template is 80 μm, and the cracking grid line width is 4-8 μm; Step 3: Place the semi-finished product obtained in step 2 on the sample stage of the magnetron sputtering system and pump the background vacuum of the magnetron sputtering system to 1.0×10 -3 Pa, high-purity (99.999%) argon gas was introduced, the pressure was adjusted to 1.0 Pa, the distance between the fixed target and the substrate was 10 cm, the sputtering power was 100 W, the ceramic BaSnO3 target was sputtered to obtain a 50 nm thick BaSnO3 film, and the deposition temperature was room temperature; Step 4: Use acetone and ultrasonic cleaning to remove the self-cracking film on the copper film. After cleaning, a BaSnO3 grid can be obtained; Step 5: Spray the etching solution evenly onto the surface of the BaSnO3 grid and seal it for 10 minutes. The etching solution used is a 10% FeCl3 solution. The etching temperature is controlled at 40°C. After etching, it is washed with deionized water and alcohol to remove the etching solution to obtain a transparent conductive film with a double-layer grid structure.
[0033] Example 6 A method for preparing a transparent conductive film having a double-layer grid structure mainly comprises the following steps: Step 1: Clean the transparent flexible substrate (flexible glass) with alcohol and acetone. After the transparent flexible substrate is dried, use pulsed laser deposition technology to prepare a copper film on the surface of the flexible glass substrate. When performing pulsed laser deposition, the background vacuum is pumped to 1.0×10 -3 Pa, the distance between the target and the substrate was fixed at 5 cm, the laser energy was 300 mJ, the frequency was 5 times / second, and a 100 nm thick copper film was deposited; Step 2: A self-cracking agent is selected from silicone acrylic emulsion, and a self-cracking film with a thickness of 9 μm is prepared on the surface of the copper film by spin coating, and dried at a temperature of 30° C. to allow the self-cracking film to naturally crack to form a mesh cracking template; the average mesh diameter of the cracks in the mesh cracking template is 80 μm, and the cracking grid line width is 4-8 μm; Step 3: Place the semi-finished product obtained in step 2 on the sample stage of the magnetron sputtering system and pump the background vacuum of the magnetron sputtering system to 1.0×10 -3 Pa, high-purity (99.999%) argon gas was introduced, the pressure was adjusted to 1.0 Pa, the distance between the fixed target and the substrate was 10 cm, the sputtering power was 100 W, the ceramic BaSnO3 target was sputtered to obtain a 100 nm thick BaSnO3 film, and the deposition temperature was room temperature; Step 4: Use acetone and ultrasonic cleaning to remove the self-cracking film on the copper film. After cleaning, a BaSnO3 grid can be obtained; Step 5: Spray the etching solution evenly onto the surface of the BaSnO3 grid and seal it for 10 minutes. The etching solution used is a 10% FeCl3 solution. The etching temperature is controlled at 40°C. After etching, it is washed with deionized water and alcohol to remove the etching solution to obtain a transparent conductive film with a double-layer grid structure.
[0034] Comparative Example 1 A method for preparing a conductive film mainly comprises the following steps: Step 1: Clean the transparent flexible substrate (transparent flexible plastic) with alcohol and dry it; Step 2: A self-cracking agent is selected from acrylic emulsion, and a self-cracking film with a thickness of 10 μm is prepared on the surface of the copper film by a pull-up coating method, and the film is dried at a temperature of 60° C., so that the self-cracking film naturally cracks to form a mesh cracking template; the average mesh diameter of the cracks in the mesh cracking template is 60 μm, and the cracking grid line width is 4-7 μm; Step 3: After the transparent flexible substrate is dried, a copper film is prepared on the surface of the transparent flexible substrate by using a magnetron sputtering coating method. When performing the magnetron sputtering coating, the background vacuum of the magnetron sputtering system is evacuated to 1.0×10 -3 Pa, high-purity (99.999%) argon gas was introduced, the pressure was adjusted to 1.0 Pa, the distance between the target and the substrate was fixed at 10 cm, the sputtering power was 100 W, and the metal copper target was sputtered to obtain a 100 nm thick copper film; Step 4: Use acetone and ultrasonic cleaning to remove the self-cracking film on the copper film. After cleaning, a copper grid can be obtained.
[0035] First, the transmittance and sheet resistance of the products obtained in Examples 1-6 were tested, wherein the average transmittance of the obtained products in the visible light band was tested using an ultraviolet-visible spectrophotometer. The sheet resistance of the obtained products was tested using a four-probe resistance test system. The results are shown in Table 1.
[0036] Table 1 Transmittance and sheet resistance of the products obtained in Examples 1-6 As shown in Table 1, the light transmittance of the transparent conductive film prepared by the method of the present invention is greater than 80%, and the sheet resistance can be as low as 4Ω / sq, indicating that it has high light transmittance and low sheet resistance. For optoelectronic devices, especially large-area display devices, this can effectively improve device stability and display effects, and reduce internal resistance heat loss.
[0037] Next, the resistance change rate of the products obtained in Examples 1-6 and Comparative Example 1 was analyzed, and the resistance change rate of the products obtained was tested in an accelerated aging test environment at a temperature of 85°C and a relative humidity of 85%, with different durations (24 hours and 240 hours). The results are shown in Table 2.
[0038] Table 2 Resistance change rate of the products obtained in Examples 1-6 and Comparative Example 1 As shown in Table 2, the common film (such as that prepared in Comparative Example 1) loses its conductivity after 24 hours. However, the resistance change rate of the transparent conductive film prepared in the present invention is not higher than 5% after 240 hours, indicating that the transparent conductive film of the present invention has good stability.
[0039] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a transparent conductive film having a double-layer grid structure, characterized in that: The following steps are involved: Step 1: Clean the transparent flexible substrate, and after the transparent flexible substrate is dried, prepare a copper film on the surface of the transparent flexible substrate by using vacuum coating technology; Step 2: using a self-cracking agent to prepare a layer of self-cracking film on the surface of the copper film, drying it at room temperature to 80° C., so that the self-cracking film naturally cracks to form a mesh-like cracking template; Step 3, using magnetron sputtering technology to prepare a layer of BaSnO3 film on the mesh cracking template; Step 4: Use acetone and ultrasonic cleaning to remove the self-cracking film on the copper film, thereby obtaining a BaSnO3 grid; Step 5: Spray etching solution onto the surface of the BaSnO3 grid and seal it to let it stand to etch the copper film into a copper grid, thereby obtaining a transparent conductive film with a double-layer grid structure.
2. The method for preparing a transparent conductive film having a double-layer grid structure according to claim 1, characterized in that: In step 1, the transparent flexible substrate is a flexible glass or a flexible transparent plastic with a thickness of 30-120 μm.
3. The method for preparing a transparent conductive film having a double-layer grid structure according to claim 1, characterized in that: In step 1, the vacuum coating technology is magnetron sputtering coating, thermal evaporation coating or pulsed laser deposition.
4. The method for preparing a transparent conductive film having a double-layer grid structure according to claim 1, characterized in that: In step 2, the self-cracking agent is any one of pure acrylic emulsion, silicone acrylic emulsion, acrylic acid emulsion or nail polish.
5. The method for preparing a transparent conductive film having a double-layer grid structure according to claim 1, characterized in that: In step 2, the thickness of the self-cracking film is 5-15 μm.
6. The method for preparing a transparent conductive film having a double-layer grid structure according to claim 1, characterized in that: In step 2, a self-cracking film is prepared by a Czochralski coating method or a spin coating method.
7. The method for preparing a transparent conductive film having a double-layer grid structure according to claim 1, characterized in that: In step three, a layer of BaSnO3 film is prepared on the mesh cracking template and on the outer peripheral surface of the copper film using magnetron sputtering technology.
8. The method for preparing a transparent conductive film having a double-layer grid structure according to claim 1, characterized in that: In step five, the etching solution is evenly sprayed on the surface of the BaSnO3 grid and sealed and allowed to stand for 2 to 10 minutes. The etching solution used is a FeCl3 solution with a concentration of 10 to 40%. The etching temperature is controlled at 40 to 60°C. After the etching is completed, it is cleaned with deionized water and alcohol to remove the etching solution.
9. A transparent conductive film having a double-layer grid structure, characterized in that: The invention comprises a transparent flexible substrate and a double-layer grid structure arranged on the transparent flexible substrate. The double-layer grid structure is composited by a copper grid and a BaSnO3 grid. The BaSnO3 grid covers the top surface of the copper grid.
10. The transparent conductive film with a double-layer grid structure according to claim 9, characterized in that: The thickness of the copper grid is 100-200 nm, and the thickness of the BaSnO3 grid is 50-200 nm.
Citation Information
Patent Citations
Etching liquid composition and etching method
CN103046050A
Preparation method for high-haze composite transparent conductive electrode
CN105355675A
Sandwich structure transparent conductive thin-film and preparation method thereof
CN105489270A
Flexible transparent electrode and fabrication method thereof
CN105741916A
Preparation method of wear-resistant inorganic non-stick coating
CN118166313A
Cited By
Super wear-resistant hydrophobic AG glass and preparation method thereof
CN120309193A
A super wear-resistant hydrophobic AG glass and its preparation method
CN120309193B
Silver nanowire composite citric acid cross-linked chitosan transparent conductive film and preparation method thereof
CN120613193A